The effectiveness of supplementary arm and upper body exercises following total hip arthroplasty for osteoarthritis in the elderly: a randomized controlled trial. (July 2017) - Mitrovic, Dragica; Davidovic, Mladen; Erceg, Predrag; Marinkovic, Jelena
Objective: To determine whether arm and upper body exercises in addition to the standard rehabilitation programme improve outcomes after hip arthroplasty. Design: Prospective, parallel, randomized, controlled trial. Setting: Orthopaedic and rehabilitation departments. Subjects: A total of 70 patients >60 years of age, who underwent hip replacement, out of 98 eligible candidates after exclusion criteria were implemented. Interventions: The study group took part in the supplementary arm and upper body exercise programme to be compared with the standard rehabilitation programme group. Main outcome: The primary outcome was a Harris Hip Score. Secondary outcomes were: Hand grip strength and Medical Outcomes Study 36-Item Short-Form Health Survey. Outcomes were assessed preoperatively, two weeks after surgery and at 12 weeks follow-up. Results: In the intervention group, significant improvements were found: in functional ability – Harris Hip Score after two (mean difference = 4.7 points) and 12 (mean difference = 5.85 points) weeks; in muscle strength – handgrip for both hands (mean difference for dominant hand = 4.16 and for the other hand = 2.8) after 12 weeks; and in role–physical dimension SF-36 Health Survey (mean difference = 6.42 points) after 12 weeks. Conclusion: Results of this study indicate that arm and upper body exercises in addition to the standard rehabilitation programme improve outcomes 12 weeks after hip arthroplasty.